2017
DOI: 10.1002/jhbp.445
|View full text |Cite
|
Sign up to set email alerts
|

A primary tumor of mixed histological type is a novel poor prognostic factor for patients undergoing resection of liver metastasis from gastric cancer

Abstract: Histological evaluation of primary tumors may aid to identify patients suitable for undergoing surgical resection of liver metastasis from gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…For liver metastases from gastric cancer, no reports of RCTs were found. A meta‐analysis of the 5‐year survival rate was performed using data from five of the reported retrospective cohort studies 22–26 and incorporated into this set of guidelines; our meta‐analysis showed that giving chemotherapy after hepatectomy for liver metastases from gastric cancer increased the 5‐year survival rate more than hepatectomy alone.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For liver metastases from gastric cancer, no reports of RCTs were found. A meta‐analysis of the 5‐year survival rate was performed using data from five of the reported retrospective cohort studies 22–26 and incorporated into this set of guidelines; our meta‐analysis showed that giving chemotherapy after hepatectomy for liver metastases from gastric cancer increased the 5‐year survival rate more than hepatectomy alone.…”
Section: Resultsmentioning
confidence: 99%
“…For liver metastases from gastric cancer, no reports of RCTs were found. A meta-analysis of the 5-year survival rate was performed using data from five of the reported retrospective cohort studies [22][23][24][25][26] and incorporated into this set of guidelines; our meta-analysis showed that giving chemotherapy after hepatectomy for liver metastases from gastric cancer increased the 5-year survival rate more than hepatectomy alone. Overall 3-year and 5-year survival rates of conversion hepatectomy, i.e., hepatectomy in patients where the cancer was converted from an unresectable to resectable state by chemotherapy, would be better compared with those of chemotherapy alone for unresectable colorectal cancer (clinical question 14).…”
Section: Liver Metastasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies from the Far East have shown more aggressive clinical behavior and worse survival in the mixed type, but mainly for early GC [ 28 , 29 ]. Even though it seems that the mixed type does not influence the OS when compared to the diffuse type in both early and advanced GC [ 28 , 30 ], mixed type histology has been indicated as a poor prognostic factor [ 31 ]. Aggressive biological features of mixed type GC include high Ki-67 proliferation index, and abnormal expression of E-cadherin and vascular endothelial growth factor (VEGF) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this retrospective study, we investigated whether a UDT component within MT early gastric cancers could be recognized preoperatively, since the presence of a UDT component profoundly affects the clinical course and treatment decision of early gastric cancers. Some retrospective studies of surgical cases reported a higher probability of lymph node metastasis[ 16 - 20 ] and even poorer prognosis[ 21 - 24 ] in MT gastric cancers, while other studies have reported that these relationships may not apply to MT gastric cancers that meet the criteria for endoscopic curative resection[ 25 , 26 ]. However, retrospective studies of surgical cases tend to ignore the uncertainty of a preoperative diagnosis.…”
Section: Discussionmentioning
confidence: 99%